Question
upstudy study bank question image url

379 1) \( \lg \left(x^{2}-2 x\right)=\lg 30-1 \)

Ask by Floyd Schofield. in Kazakhstan
Feb 10,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Решение уравнения \( \lg(x^{2} - 2x) = \lg 30 - 1 \) приводит к \( x = 3 \) и \( x = -1 \).

Solution

Рассмотрим уравнение:   lg(x² – 2x) = lg 30 – 1. Заметим, что число 1 можно записать как lg 10, поскольку lg 10 = 1. Тогда правая часть:   lg 30 – 1 = lg 30 – lg 10 = lg(30/10) = lg 3. Таким образом, уравнение принимает вид:   lg(x² – 2x) = lg 3. Так как функция логарифма обратима на положительной области определения, при условии x² – 2x > 0 получаем равенство аргументов:   x² – 2x = 3. Переносим 3 в левую часть:   x² – 2x – 3 = 0. Найдём корни данного квадратного уравнения. Для этого определим дискриминант:   D = (–2)² – 4·1·(–3) = 4 + 12 = 16. Так, корни уравнения:   x = [2 ± √16] / 2 = [2 ± 4] / 2. Получаем два решения:   x₁ = (2 + 4)/2 = 6/2 = 3, x₂ = (2 – 4)/2 = (–2)/2 = –1. Проверим, удовлетворяют ли они ограничению x² – 2x > 0:   Для x = 3: 3² – 2·3 = 9 – 6 = 3 > 0.   Для x = –1: (–1)² – 2·(–1) = 1 + 2 = 3 > 0. Оба решения удовлетворяют условию области определения. Ответ: x = 3 и x = –1.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the equation \( \lg \left(x^{2}-2 x\right) = \lg 30 - 1 \), we can first rewrite the right side. Recall that \( \lg a - b = \lg(a/10^b) \), thus: \[ \lg \left(x^{2}-2 x\right) = \lg \left(\frac{30}{10^1}\right) = \lg 3 \] Since the logs are equal, we can drop the logarithm (assuming the arguments are positive) to set the insides equal to each other: \[ x^{2} - 2x = 3 \] Rearranging gives us the quadratic equation: \[ x^{2} - 2x - 3 = 0 \] Now we can factor this equation: \[ (x - 3)(x + 1) = 0 \] Setting each factor to zero gives us two potential solutions: \[ x - 3 = 0 \quad \Rightarrow \quad x = 3 \] \[ x + 1 = 0 \quad \Rightarrow \quad x = -1 \] However, we need to check these solutions in the original logarithmic equation to ensure they don't yield negative arguments: For \( x = 3 \): \[ x^{2} - 2x = 3^{2} - 2 \cdot 3 = 9 - 6 = 3 \quad \text{(valid)} \] For \( x = -1 \): \[ x^{2} - 2x = (-1)^{2} - 2 \cdot (-1) = 1 + 2 = 3 \quad \text{(valid)} \] Thus, both solutions are valid, and the final solutions are: \[ x = 3 \quad \text{and} \quad x = -1 \]

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy